A day in the life of a librarian - Burby, Liza N. (New York : PowerKids Press, 1999)
Describes a typical work day for a public librarian as he answers reference questions, repairs microfilm readers, weeds the collections, and finds videos for patrons.
Starting the day -- Detective work -- I'm looking for a book -- Walking the floor -- Homework help -- Not just books -- Weeding the books -- An elevator ride for books -- On the Web -- A fun day.
Includes glossary and index.
4.0.
4.0
K-3
Keywords: Olney, James -- Juvenile literature; Olney, James; Olney, James; Librarians -- Juvenile literature; Library science -- Juvenile literature; Library science -- Vocational guidance -- Juvenile literature; Public librarians -- Juvenile literature; Public libraries -- Reference services -- Juvenile literature; Public libraries -- Reference services -- Vocational guidance -- Juvenile literature; Reference librarians -- Juvenile literature; Reference services (Libraries) -- Juvenile literature; Reference services (Libraries) -- Vocational guidance -- Juvenile literature; Librarians; Libraries; Occupations; Librarians; Libraries; Library science; Library science -- Vocational guidance; Occupations; Public libraries; Reference services (Libraries); Reference services (Libraries) -- Vocational guidance